Analytical modelling of high strength concrete columns under ambient and fire conditions. (15th November 2021) - Du, Panwei; Yang, Yaowen; Tan, Kang Hai
Highlights: A simple yet universally applicable analytical model is developed. The proposed model has a wide range of applicability. The model can capture load–deflection curves and predict peak loads and fire resistance. Accurate and conservative predictions are achieved. Parametric studies are conducted to investigate effects of transient and creep strains. Abstract: In view of limited studies on modelling of high strength concrete (HSC) columns under fire conditions, this paper develops a simple yet universally applicable model to analyse the behaviour of HSC columns under ambient and fire conditions. The model transforms the cross-sectional capacity to actual column (structural) capacity by introducing a stability term. It incorporates heat transfer analysis, different strain components at high temperature and slenderness effect. The proposed model can be used to determine load–deflection curves and predict peak loads of RC columns at ambient temperature. Moreover, it can trace structural response (i.e. mid-height deflection) of columns under fire conditions and determine the fire endurance under any heating curve. The proposed model has a wide range of applicability for both normal strength concrete and high strength concrete with a compressive strength ranging from 24.1 MPa to 97.2 MPa. It has been validated with a large set of data including 47 specimens tested at ambient temperature and 68 specimens under fire conditions. Comparison with the test results shows that the proposed model can well capture the column mid-height deflection at ambient and elevated temperatures. Accurate and conservative predictions are achieved on peak loads at ambient temperature with a mean value of 0.96 and a COV of 0.13, and fire resistance at high temperatures with a mean value of 0.97 and a COV of 0.19.